EFEK ANTIDIARE EKSTRAK ETANOL DAUN PARIJOTO (Medinilla speciosa Blume) PADA MENCIT JANTAN GALUR BALB/C - Yance Anas; Desi Rakhmawati; Layyinatul Fuadah; Nola Carina Rahayu (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTParijoto is one of a rare plant species in Indonesia, and its leaves have traditionally been utilized to treat diarrhea in the area of Kudus Regency, Indonesia. Parijoto leaves contain active compounds of tannin and flavonoid which have antidiarrheal properties. This investigation intends to demonstrate the antidiarrheal effect of parijoto leaf ethanol extract (EEDP) on male Balb/C mice castor oil-induced diarrheal and reveal its antidiarrheal mechanism through antimotility and antisecretory testing. EEDP made by maceration method. The antidiarrheal effects of three series level EEDP (500; 1,000 and 2,000) mg / Kg BB tested on diarrhea mice induced by castor oil. Concurrently, the antimotility and antisecretory effects of EEDP investigated with the intestinal transit method and castor oil-induced enteropooling. The data in this study were the onset of diarrhea, the weight of liquid-formless stools (for 8 hours), the ratio of digestion tracts passed by norit markers, and the volume of intestinal contents. These data were analyzed statistically at the 95% confidence level. The examination presumed that EEDP was able to respite the onset of diarrhea and diminish the formation of liquid-formless feces in male Balb/C mice induced by castor oil. The antidiarrheal mechanism of EEDP also exhibited in this study through its effects as antimotility and antisecretory.Keywords: Parijoto leaf ethanol extract, antidiarrheal, antimotility, antisecretory